The Study of Consumer Perception on Indonesia Rattan Furniture as the Basic Knowledge for Strategy Formulation of Rattan Furniture Business in Indonesia - Rasyid, Mohammad Rizqi; Hudrasyah, Herry (The Indonesian Journal of Business Administration, 2014)
Abstractâ€”The purpose of this academic journal is to study the consumer perception toward Indonesian rattan furniture as the basic knowledge for strategy formulation of rattan furniture business in Indonesia. To formulate a business strategy, a sample company XYZ Furniture is used because the company has the condition that correlates with the business problems. The variables of research including product, brand equity, consumer knowledge and purchase intention. The study of these variables would become the basic knowledge for the strategy formulation.Â Keywords-component; consumer perception, strategy formulation, Indonesian rattan furniture.